2022
DOI: 10.1002/ijc.33933
|View full text |Cite
|
Sign up to set email alerts
|

Is ovarian recovery after chemotherapy in young patients with early breast cancer influenced by controlled ovarian hyperstimulation for fertility preservation or tumor characteristics? Results of a prospective study in 126 patients

Abstract: Young individuals, aged <40 years, represent 7% of all patients with early breast cancer (EBC), most of whom receive chemotherapy. Preserving future fertility in these patients has become a major concern. This prospective study assessed ovarian function during and after chemotherapy according to patient and tumor characteristics and evaluated the outcome of controlled ovarian hyperstimulation (COH).Ovarian reserve was evaluated in terms of amenorrhea duration and by longitudinal serum anti-Müllerian hormone (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…The gold standard for the diagnosis of the tumour is 100% the histopathological study, complemented by immunohistochemical analysis; the expression of the markers OCT3/4, D2-40 and SALL4 are elements of judgement that support the diagnosis of dysgerminoma in any case [18]. Dysgerminomas are generally malignancies with a good prognosis, with a high cure rate, and they are also chemo-and radiosensitive, which allows neoadjuvant protocols to be carried out in the case of giant lesions [19]. Recurrence rates are low.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for the diagnosis of the tumour is 100% the histopathological study, complemented by immunohistochemical analysis; the expression of the markers OCT3/4, D2-40 and SALL4 are elements of judgement that support the diagnosis of dysgerminoma in any case [18]. Dysgerminomas are generally malignancies with a good prognosis, with a high cure rate, and they are also chemo-and radiosensitive, which allows neoadjuvant protocols to be carried out in the case of giant lesions [19]. Recurrence rates are low.…”
Section: Discussionmentioning
confidence: 99%
“…For reasons that are not clear, patients with reproductive history were more likely to develop POI after chemotherapy. There have been previous studies on the types and molecular characteristics of breast cancer and ovarian function after chemotherapy, but the effect of breast cancer stage on ovarian function is rarely mentioned [ [32] , [33] , [34] , [35] ]. We found that compared with patients with pathological stage Ⅱ or Ⅲ disease, patients with stage Ⅰ disease had a lower risk of POI and were more likely to recover from temporary impairment of ovarian function, which may be related to systemic changes in the natural course of breast cancer, suggesting that patients with earlier stages of disease have better body function, including ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…AMH measures were performed using the Roche Elecsys AMH Plus assay in both centers with a limit of detection (LOD) of 0.01 ng/ml. without letrozole, before administration of chemotherapy in an adjuvant setting (cCOH) [19].…”
Section: Patient Populationmentioning
confidence: 99%
“…All as recommended for standard COH protocol [13]. In the cCOH group, ovulation triggering was performed with GnRHa (0.2 mg), hCG (6,500 IU) or dual trigger (GnRHa 0.2mg and hCG 1,500 IU) 7 mm and a majority of intermediary , based on standard practice [19].…”
Section: Coh Protocolsmentioning
confidence: 99%